NEUROLOGICAL DISEASE AS COMPLICATIONS OF COVID-19: : A LITERATURE REVIEW - Tadeu Guardia Júnior, Marcos; Espírito Santo Campos, Nathália; Steven Philippart, Kevin; Sayuri Shiraishi, Letícia; Domingos Ribeiro, Lucas; Ventura Tauyr, Luciana (Health and Society, 2021)
Neurological complications are very relevant in the current pandemic scenario. The virus has the Spike protein, which binds to the Angiotensin-Converting Enzyme 2 receptor (ACE2), receptor present in the body, triggering the infection. This enzyme is present in abundance in the respiratory epithelium, which explains the predominance of respiratory symptoms; however it is still found in neurons and glial cells, making the Central Nervous System (CNS), a possible target of the pathogen. The objective is to highlight the main neurological complications resulting from infection by the coronavirus agent of acute respiratory syndrome (SARS-CoV-2). Thus, we conducted a literature search based on the descriptors “Covid 19”, “Neurological disease” and “Complications”, with publication period between 2020 and 2021 on the MEDLINE, PubMed, Latin American and Caribbean Literature in Science Sciences platforms (LILACS), UpToDate and World Health Organization. The most persistent neurological complications found were: aphasia, dysgeusia, cerebrovascular diseases and encephalopathies. The neurological manifestations arising from COVID-19 are a reality and very complex , so further studies are needed to further evaluation and analysis of the consequences caused by this virus infection.